Analisis Pengendalian Persediaan Bahan Baku PVC Compound Menggunakan Metode ABC Analisis dan EOQ Berbasis POM-QM for Windows V5.2 - Amin Widodo; Makhsun Makhsun; Achmad Hindasyah (Teknik Informatika Universitas Pamulang, 2020)
PT. Sinarmonas Industries is engaged in the Manufacture industry as a precision cable company that manufactures PVC Compound itself, the company is committed to always maintaining customer satisfaction by implementing ISO 9001 2015. In an effort to increase customer satisfaction the company experiences constraints namely determining raw materials that require special monitoring so that more inventory control efficient. The research method used is the ABC Analysis and Economic Order Quantity (EOQ) method with the help of POM-QM Information Technology Tools for Windows V5.2 this software is to assist companies in solving problems faced by operations management. The results of the study using the ABC Analyst method show that raw materials that require very strict monitoring, namely PVC 66, stabilizer, and PVC 71 of the three raw materials, are calculated using the Economic Order Quantity (EOQ) method, the company has the benefit of saving the cost of raw material inventory, namely PVC 66 an average of Rp 96,321,440.00 or companies can save inventory costs by 44%, Stabilizer raw materials an average of Rp 4,634,959.00 or companies can save inventory costs by 57%, PVC raw materials 71 an average of Rp 49,304 .566.00 or a company can save 38% in costs.